Effects of Speed, Agility, and Quickness (SAQ) training on soccer player performance—a systematic review and meta-analysis - Sun, Min; Soh, Kim Geok; Ma, Shuzhen; Wang, Xinzhi; Zhang, Junlong; Yaacob, Azhar (Public Library of Science, 2025)
Background Previous studies have reported on the impact of Speed, Agility, and Quickness (SAQ) training on the performance of soccer players. However, there is still controversy regarding the results. This systematic review and meta-analysis aim to accurately assess the effects of SAQ training on the performance of soccer players. Methods We conducted a comprehensive search on March 15, 2024, using Web of Science, PubMed, Scopus, and EBSCOhost. Eligibility criteria for selecting studies were established based on the PICOS framework: (i) Population—healthy soccer players; (ii) Intervention—SAQ training; (iii) Comparison condition (conventional training or traditional training); (iv) Outcome—physical performance (speed, agility, strength, etc.); (v) Study design—randomized controlled trials. The PEDro scale was employed to evaluate the methodological quality of each study, and a random-effects model was used for the meta-analysis. Results A total of 11 studies met the inclusion criteria for the systematic literature review. One study with low PEDro score was excluded, and one was excluded based on Cochrane bias risk assessment. Finally, 9 studies were included in the meta-analysis, comprising 498 soccer players. Overall, the results indicated a significant impact of SAQ training on physical qualities and dribbling speed among soccer players. Specifically, there was a moderate effect size for sprint performance (5m, 10m, 20m) (ES = 0.75; p < 0.01), change of direction ability (COD) (ES = 0.35; p < 0.001), power (vertical and horizontal jumps) (ES = 0.67; p < 0.01), while flexibility showed no significant impact (ES = 0.11; p > 0.05). Moreover, change-of-direction dribbling demonstrated a significant effect (ES = 0.58; p < 0.01). Conclusion Overall, SAQ training effectively enhances speed, COD, explosiveness, and change-of-direction dribbling specific performance in adolescent soccer players, particularly in sprinting. However, it does not have an advantage in improving flexibility. Further high-quality studies encompassing a broader range of exercises are needed to fully determine the effectiveness of SAQ training in improving other physical qualities and technical skills of soccer players, as well as ultimately enhancing match performance.